2004
DOI: 10.1023/b:emas.0000029899.31965.33
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Status of Visakhapatnam (India) – Indices Basis

Abstract: Industrial development in Visakhapatnam is conspicuous to urban agglomeration and the city is located in a topographical bowl formed by two-hill ranges. A major portion of the city is within the bowl area wherein most of the industrial and commercial activities are existing and lies within a distance of 10 km from the shore of the Bay of Bengal. Due to the peculiar geographic location of city, wind movement is either eastern or western and is engulfed within the hill ranges. Hence, there is a possibility of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The high NO 2 concentrations, combined with the intensive UV radiations in subtropical Indian conditions, results in photochemical smog with high O 3 concentration, which can adversely affect human health. Singh et al (1997) and Reddy et al (2004) also observed this phenomenon in New Delhi and Vishakhapatnam, respectively. A relative fall in TSPM, PM 10 , SO 2 and NO 2 levels during post-monsoon may be due to the "scrubbing off" of these air pollutants by monsoon rains.…”
Section: Seasonal Variationsmentioning
confidence: 63%
“…The high NO 2 concentrations, combined with the intensive UV radiations in subtropical Indian conditions, results in photochemical smog with high O 3 concentration, which can adversely affect human health. Singh et al (1997) and Reddy et al (2004) also observed this phenomenon in New Delhi and Vishakhapatnam, respectively. A relative fall in TSPM, PM 10 , SO 2 and NO 2 levels during post-monsoon may be due to the "scrubbing off" of these air pollutants by monsoon rains.…”
Section: Seasonal Variationsmentioning
confidence: 63%
“…Air pollution indices are useful as they indicate day to day change in air quality status. Air pollution index (API)/ Air quality index (AQI) is a scheme that transform the weighted values of individual air pollutant species (one or more) in a single number (Reddy et al, 2004). Therefore, Oak Ridge Air Quality Index (ORAQI), and Air pollution index (API)/ Air quality index (AQI) can be used as a tool to report overall environmental status.…”
Section: Resultsmentioning
confidence: 99%
“…Halliwell et al (1999) stressed that excess intake of NO2 could enhance in-vivo production of peroxynitrite, oxidative stress, other metabolic diseases and cancers (Choudhari et al, 2013). The higher level of NO2 emitted by landfills could also cause acid rains, skin diseases and damaged roofing sheets (Reddy et al, 2004). Elevated levels of CO in the landfills and communities 100M away from the landfills could pose dangers to the inhabitants of the landfill communities.…”
Section: Discussionmentioning
confidence: 99%